Comparative pharmaceutical metabolism by rainbow trout (Oncorhynchus mykiss) liver S9 fractions. (21st June 2013) - Connors, Kristin A.; Du, Bowen; Fitzsimmons, Patrick N.; Hoffman, Alex D.; Chambliss, C. Kevin; Nichols, John W.; Brooks, Bryan W.
Abstract: The occurrence of pharmaceuticals in the environment presents a challenge of growing concern. In contrast to many industrial compounds, pharmaceuticals undergo extensive testing prior to their introduction to the environment. In principle, therefore, it may be possible to employ existing pharmacological safety data using biological "read‐across" methods to support screening‐level bioaccumulation environmental risk assessment. However, few approaches and robust empirical data sets exist, particularly for comparative pharmacokinetic applications. For many pharmaceuticals, the primary cytochrome P450 (CYP) enzymes responsible for their metabolism have been identified in humans. The purpose of the present study was to employ a comparative approach to determine whether rainbow trout biotransform pharmaceuticals known to be substrates for specific human CYPs. Seven compounds were selected based on their primary metabolism in humans by CYP3A4, CYP2D6, or CYP2C9. Five additional test compounds are known to be substrates for multiple CYPs. Metabolism by rainbow trout liver S9 fractions was evaluated using a substrate‐depletion approach, which provided an estimate of intrinsic hepatic clearance (CLIN VITRO, INT ). An isotope dilution liquid chromatography–tandem mass spectrometry method was employed for quantitation of parent chemical concentrations. Only 2 general CYP substrates demonstrated measurable levels of substrate depletion. No significant biotransformation was observed for known substrates of human CYP2D6, CYP2C9, or CYP3A4. The results of this study provide novel information for therapeutics that fish models are likely to metabolize based on existing mammalian data. Further, these results suggest that pharmaceuticals may possess a greater tendency to bioaccumulate in fish than previously anticipated. Environ Toxicol Chem 2013;32:1810–1818. © 2013 SETAC